Assessing UNGC pharmaceutical signatories stakeholders using big data. (6th May 2019) - Zilic, Ivana; LaVan, Helen; Cook, Lori S.
Abstract: This article aims to focus on how signatories versus nonsignatories in the U.S. pharmaceutical sector compare with respect to the internal and external stakeholders and principles of the United Nations Global Compact (UNGC). We seek to answer the question: Do signatories to the UNGC walk the talk better than nonsignatories as determined by a variety of published rankings and data? This research presents an innovative approach to the evaluation of UNGC signatories. It uses several objective and independent data sources to assess a matched group of signatories versus nonsignatories in the U.S. pharmaceutical sector. Signatory organizations in the same sector as determined by SIC codes were matched with nonsignatories on variables such as size and number of employees in U.S. pharmaceutical companies. Then both types of organizations were compared on the following data sources: Coalition for Environmentally Responsible Economies ratings, ratings by external stakeholders, ratings by employees, unionization data, financial measures, and annual reports to shareholders. Using nonparametric testing the research found there are differences between signatories and nonsignatories in the U.S. pharmaceutical sector for some of the external stakeholder measures and no differences were found for the internal stakeholder measures.